2020
DOI: 10.1093/cid/ciaa365
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Partial Oral Antibiotic Treatment for Persons Who Inject Drugs and Are Hospitalized With Invasive Infections

Abstract: Abstract Background Persons who inject drugs (PWID) are at risk of invasive infections; however, hospitalizations to treat these infections are frequently complicated by against medical advice (AMA) discharges. This study compared outcomes among PWID who (1) completed a full course of inpatient intravenous (IV) antibiotics, (2) received a partial course of IV antibiotics but were not prescrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…Patients with endocarditis, considered to be the most complicated infection of those evaluated—and universally fatal if untreated, were also most likely to leave the hospital prior to completing treatment. Many patients with IDU-associated infections and patient-directed discharge do not receive oral antibiotics to complete their treatment [ 11 ]; in one study, those who did not receive oral antibiotics upon patient-directed discharge had a 90-day readmission rate more than double of those with patient-directed discharge who did have an antibiotic prescribed (69% versus 33%) [ 39 ]. Avoidance of patient-directed discharge should be a top priority for patients with IDU-associated infections.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with endocarditis, considered to be the most complicated infection of those evaluated—and universally fatal if untreated, were also most likely to leave the hospital prior to completing treatment. Many patients with IDU-associated infections and patient-directed discharge do not receive oral antibiotics to complete their treatment [ 11 ]; in one study, those who did not receive oral antibiotics upon patient-directed discharge had a 90-day readmission rate more than double of those with patient-directed discharge who did have an antibiotic prescribed (69% versus 33%) [ 39 ]. Avoidance of patient-directed discharge should be a top priority for patients with IDU-associated infections.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, even partial treatment may be better than none; one study in PWID leaving AMA showed that receipt of sub-par oral antimicrobials for invasive infections resulted in lower readmission rates [ 28 ]. Furthermore, dalbavancin confers the probable benefit of directly observed therapy, which is generally not possible for outpatient oral microbial regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Although recent randomized trials have demonstrated that oral antibiotics are effective for bone and joint infections and endocarditis, these studies have included few patients with substance use disorders, and concerns about nonadherence may limit use of oral therapy in this population [ 5 , 6 ]. A recent retrospective study showed similar readmission rates among PWID with invasive infections who completed inpatient parenteral therapy and those who received partial oral therapy, but published evidence with oral therapy in this population remains scarce [ 7 ]. Novel care models to successfully treat these patients while shortening durations of hospitalization are urgently needed.…”
Section: Introductionmentioning
confidence: 99%